Analisis Yuridis tentang Aktivitas Pembelian Bahan Bakar Minyak (BBM) di SPBU Menggunakan Jeriken untuk Dijual Kembali Ditinjau dari Undang-Undang Nomor 22 Tahun 2001 tentang Minyak dan Gas Bumi - Sulastri Sonbai Feto; Rudepel Petrus Leo; Debi F. Ng. Fallo (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
Law Number 22 of 2001 concerning Oil and Gas that oil and gas business activities are divided into two, namely upstream business activities and downstream business activities. The activity of buying and selling fuel oil is usually in retail form which is put in a glass bottle with a liter size that will be sold to buyers who have previously been bought by sellers from gas stations where fuel oil (BBM) is one of the important elements in fulfilling the community's economy. Based on the initial observations of researchers, especially in Kupang City, retail fuel oil sellers cannot be calculated so much and usually, these retail fuel oil sellers sell in front along the road or in ordinary places, vehicles pass by by setting up mini kiosks or workshops. Therefore, researchers formulate the main problems, namely: (1) How is the implementation of legal regulations related to the act of purchasing fuel oil (BBM) at gas stations using jerry cans for resale in terms of Law Number 22 of 2001 concerning Oil and Gas? (2) What are the factors that hinder the police in handling the activity of purchasing fuel oil (BBM) using jerry cans at gas stations in terms of Law Number 22 of 2001 concerning Oil and Gas? This research is a research that uses the Empirical Juridical method. This research is a legal research conducted by researching regulations, primary data, documentation studies. The research aspects studied are Law Number 22 of 2001 concerning Oil and Gas, legal factors, law enforcement factors, facilities and facilities factors, community factors, buying and selling fuel oil, cultural factors. The results of the study found that: (1) Law Number 22 of 2001 concerning Oil and Gas in its implementation has not run well and is less firm against people who abuse fuel oil (BBM); (2) Factors that become obstacles for the police in handling fuel purchase activities are legal factors, law enforcement factors, facilities and facilities factors, community factors and cultural factors.